STUDI KASUS PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BERBASIS KEARIFAN LOKAL BUDAYA YANG ADA DI SDN LARANGAN 6 KOTA TANGERANG - Azayya Syafinka; Ina Magdalena; Rizki Zuliani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores how SDN Larangan 6, Tangerang City, uniquely instills the values of the Pancasila Student Profile (P5) through projects rooted in local wisdom. Adopting a descriptive qualitative approach with a post-positivist lens, the research highlights the pivotal roles of the school principal and a teacher as key facilitators. Data were collected through in-depth interviews, direct observations, and documentation of school activities. Findings reveal that P5 planning is carried out collaboratively among the school, teachers, students, and the school committee, covering theme selection, creation of culturally-based modules, and scheduling aligned with students’ characteristics. Creative activities such as traditional dances, batik making, handicrafts, and visits to local artisans effectively instill values of cooperation, independence, tolerance, diversity, creativity, and critical thinking. Through this approach, character education transcends theory, becoming a lived experience for students. Overall, locally-based P5 projects successfully foster holistic student character development, aligning with the dimensions of the Pancasila Student Profile and supporting the spirit of the Merdeka Curriculum, which emphasizes contextual, culturally-rooted education